The impact of the glycemic index and glycemic load of food products on human health - Bator, Ewa; Bronkowska, Monika; Bienkiewicz, Maciej; Biernat, Jadwiga (Journal of Medical Science, 2014)
The supply of carbohydrates, contained in food products and meals, to the organism causes an increase of glucose in blood, which is referred as “glycemic effect”. The concentration of glucose in blood increases after eating each meal and usually reaches its maximum after 20–30 min after food consumption, and then is gradually reduced. It returns to the level of fasting within 1–2 hours. However this pattern shows some individual variation.The increase of interest of the glycemic index and glycemic load of food products came through the interconnection of these indicators of noncommunicable chronic diseases like diabetes, cardiovascular disease, cancer, overweight and obesity.